Vrozený pakloub klícní kosti u chlapce se syndromem Prader-Willi - Sponer, P; Neumann, D; Karpas, K (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2008)
The authors present the case of a boy with congenital pseudoarthrosis of the right clavicle who met all clinical and auxologic criteria of Prader-Willi's syndrome. Poor cooperation due to mental retardation was the reason for the primary conservative treatment. During this, deformity of the middle clavicle progressed, but without development of subjective complaints and functional deficit. At his 16 years, this cosmetic defect became unacceptable for his parents and, later than it is usually recommended, resection of pseudoarthrosis with plate osteosynthesis and autologous spongioplasty was indicated. The sufficient skeletal maturation and size of both fragments allowed us to perform stable osteosynthesis with the use of a contoured reconstruction plate, without the risk of insufficient osteosynthesis or clavicle fracture after the removal of osteosynthetic material.
Keywords: klíční kost; předškolní dítě; Clavicle; Praderův-Williho syndrom; Humans; Pseudarthrosis; mužské pohlaví; Male; lidé; Child, Preschool; pseudoartróza; Prader-Willi Syndrome